KESULITAN REGULASI EMOSI PADA DEWASA AWAL DENGAN MODERATE DEPRESSION - Sya'diyah, Halimah; Ninin Retno Hanggarani; Ariyanti, Abidin Fitri (Universitas Brawijaya, 2022)
Depression is a common psychological problem that is quite significant in early adulthood. Based on several studies, depression is influenced by difficulty in emotion regulation. Based on existing research, still limited, which explained how difficulties to regulate emotions in early adult individuals with moderate depression. This study aims to describe the difficulties in early adults experiencing moderate depression in regulating emotions. The method used is qualitative with a phenomenological approach. There are 3 participants. Data were obtained through interviews with open questions. The results showed that individuals experiencing moderate depression responded to negative emotions by means of expressive suppression. On the other hand, there is an individual peculiarity, namely the individual's process of perceiving a way of dealing with negative emotions as a problem. Depresi merupakan masalah psikologis umum yang cukup signifikan dialami pada masa dewasa awal. Berdasarkan beberapa penelitian, depresi dipengaruhi oleh kesulitan regulasi emosi. Berdasarkan penelitian yang telah ada, belum ada yang menjelaskan bagaimana kesulitan regulasi emosi individu dewasa awal dengan moderate depression. Penelitian ini bertujuan untuk menggambarkan kesulitan pada dewasa awal yang mengalami moderate depression dalam meregulasi emosi. Metode yang digunakan yaitu kualitatif dengan pendekatan fenomenologis. Partisipan berjumlah 3 orang. Data didapatkan melalui wawancara dengan pertanyaan terbuka. Hasil menunjukkan bahwa yang mengalami moderate depression menanggapi emosi negatif dengan cara expressive suppression. Di sisi lain, terdapat kekhasan individual, yaitu proses individu dalam mempersepsikan suatu cara menghadapi emosi negatif sebagai suatu masalah.